2021
DOI: 10.18203/2320-1770.ijrcog20213830
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and acceptability of prenatal diagnosis among pregnant women attending antenatal clinic in a tertiary health institution in Sokoto, Nigeria

Abstract: Background: Technology and advances in research have made it possible for the fetus to become a patient whose illness can be investigated, diagnosed and treated in utero. The study was aimed at assessing the knowledge and acceptability of prenatal diagnosis among pregnant women.Methods: This was a cross-sectional study carried out between December 2016 and March, 2017. Pregnant women attending antennal care clinic at the Usmanu Danfodiyo University Teaching Hospital, Sokoto (UDUTH) were recruited via convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Interestingly, our findings align with those from Turkey, where a study of 274 women reported a similar proportion (34.3%) with adequate knowledge [ 11 ]. In contrast, studies conducted in Nigeria reported lower percentages, with one study among 417 women indicating 18.5% and another among 422 women showing 17.1% [ 12 , 13 ]. Conversely, a study in Greece among 354 women found that 50.8% had adequate knowledge [ 8 ].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, our findings align with those from Turkey, where a study of 274 women reported a similar proportion (34.3%) with adequate knowledge [ 11 ]. In contrast, studies conducted in Nigeria reported lower percentages, with one study among 417 women indicating 18.5% and another among 422 women showing 17.1% [ 12 , 13 ]. Conversely, a study in Greece among 354 women found that 50.8% had adequate knowledge [ 8 ].…”
Section: Discussionmentioning
confidence: 98%
“…In Lagos, a significant majority (81.3%) expressed a belief in the necessity of offering these tests to all expectant mothers, with a substantial proportion (75.1%) indicating a willingness to pursue further diagnostic testing if initial screening results raised concerns [15]. Similarly, studies in Greece, Ibadan, and Sokoto, and reported high levels of acceptability, with percentages ranging from 68% to 95.2% [13,16,17]. In the research conducted in Saudi Arabia, participants expressed their endorsement of government-operated facilities aimed at providing genetic testing or screening services to the country's citizens [18].…”
Section: Discussionmentioning
confidence: 99%
“…Chioma et al in South-south Nigeria observed that there is still a gap in knowledge and utilization of PD by at risk couples [6]. Ahmed et al in North-western Nigeria observed that there was overall poor knowledge of PD among pregnant women attending antenatal clinic, and the level of education was a key identifiable factor that determined knowledge and acceptability of PD [25]. Ademosun et al in South-western Nigeria reported that very few (20%) have adequate knowledge about PD as an existing control measure for sickle cell births [2].…”
Section: Prenatal Diagnosismentioning
confidence: 99%